Host genetics and tuberculosis susceptibility - Selvaraj, P. (Current science (Bangalore), 2004)
Susceptibility to tuberculosis is multifactorial. The importance of host genetic factors on the susceptibility or resistance to tuberculosis has been emphasized by many workers. Host genetic factors such as human leucocyte antigens (HLA) and non-HLA genes that are associated with the susceptibility to tuberculosis will serve as genetic markers to predispose or predetermine the development of the disease. Such markers may be useful to understand the immune mechanism of susceptibility or resistance to tuberculosis. Association of various HLA and non-HLA genes with susceptibility to tuberculosis in various ethnic population has been established. HLA studies carried out in the Asian region, especially in India, revealed the association of HLA-DR2 and -DQ1 antigens with the susceptibility to pulmonary TB. Further, studies on DNA typing explored the association of DRB1 *1501 and *1502 (DR2 subtypes) in north Indian and DRB1 *1501, DRB1 *0601 (DQ1 subtype) and DPB1 *02 (DP2 subtype) in south Indian population. Various studies on non-classical major histocompatibility complex (MHC) genes and non-MHC/non-HLA gene polymorphisms such as transporter associated with antigen processing (TAP), tumour necrosis factor α and β (TNF α and β), mannose binding lectin (MBL), vitamin D receptor (VDR) (BsmI, ApaI, TaqI and FokI polymorphisms), Interleukin-1 receptor antagonist (IL-1RA) and natural resistance associated macrophage protein-1 (NRAMP-1) genes revealed the association of TAP2 gene variant along with HLA–DR2 and functional mutant homozygotes (FMHs) of MBL with the susceptibility to pulmonary TB. The polymorphic BsmI, ApaI, TaqI and FokI gene variants of VDR showed differential susceptibility and resistance with male and female subjects. These studies suggest that multicandidate genes are associated with the susceptibility to pulmonary tuberculosis in India.